2011
DOI: 10.1017/s0025315410002134
|View full text |Cite
|
Sign up to set email alerts
|

Atlantic Multidecadal Oscillation (AMO) and sea surface temperature in the Bay of Biscay and adjacent regions

Abstract: Little information is available on the maternal -embryonic relationships among sharks. Birdbeak dogfish (Deania calcea) has been described as ovoviviparous, but this term comprises a wide range of forms on how the embryos are nourished including lecithotrophy and matrotrophy. To evaluate the maternal -embryonic relationship in birdbeak dogfish we have analysed chemical features (fatty acid composition and mercury (Hg) levels) and biological characteristics (egg and embryo dry weight variation, uterus character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 60 publications
(84 reference statements)
2
24
0
Order By: Relevance
“…A very negative North Atlantic Oscillation index will cool sea surface temperatures from the Azores region to the Bay of Biscay (Pingree, 2005;Garcia-Soto & Pingree, 2012) These positive winter NAO years are associated with shallow winter MLDs, lower seasonal amplitudes of nitrate and winter nutrient concentrations with correspondingly reduced spring time productivity as shown in the dataset (see also Jiang et al, 2013).…”
Section: Variation In Net Community Production In Relation To Nutrienmentioning
confidence: 63%
See 1 more Smart Citation
“…A very negative North Atlantic Oscillation index will cool sea surface temperatures from the Azores region to the Bay of Biscay (Pingree, 2005;Garcia-Soto & Pingree, 2012) These positive winter NAO years are associated with shallow winter MLDs, lower seasonal amplitudes of nitrate and winter nutrient concentrations with correspondingly reduced spring time productivity as shown in the dataset (see also Jiang et al, 2013).…”
Section: Variation In Net Community Production In Relation To Nutrienmentioning
confidence: 63%
“…Behrenfeld et al (2006) suggested a general trend has occurred of decreased convective mixing, increased stratification and consequent decrease in production in the Northeast Atlantic from 1999 onwards and predicts a decrease in productivity in a warming ocean. There has been a progressive warming of surface waters in the Bay of Biscay over the last 30 years (Garcia-Soto et al 2002, Somavilla et al, 2011Holt et al 2012;Taboada & Anadon, 2012, Garcia-Soto & Pingree, 2012. Winter mixing was studied extensively in Pingree & New (1989).…”
Section: Introductionmentioning
confidence: 99%
“…This may link to the stronger slope current anomaly between 1995 and 1997 on most of the shelves. The winter situation for NW Spain with respect to NAO and associated wind stress pattern is illustrated and explained in detail by Garcia-Soto and Pingree (2011). The local wind stress forcing component for the European SC is driven more effectively with a low or negative sea level pressure anomaly against the ocean margin (not in the central ocean) so we do not expect the slope current changes to have its maximum response with respect to NAO changes.…”
Section: Interannual Variabilitymentioning
confidence: 99%
“…Over the slope, the Iberian Poleward current flows towards the east and north of the Spanish and French coasts with relatively weak mean currents (~ 0.2 m.s -1 ). This current presents a marked seasonality, with stronger currents in winter that are frequently associated to positive SST anomalies over the northern Spanish slope [4,5,6,7,8,9,10]. Moreover, significant mesoscale variability has been observed along the slope, where the interaction of the current and the bathymetry gives rise to mesoscale eddies, commonly known as SWODDIES -Slope Water Eddies [5,7,11,12].…”
Section: Introductionmentioning
confidence: 99%